Digital Reform and Civil Service Performance: Empirical Evidence from the Implementation of SIASN, MyASN, and MOLA in Indonesia - Suroso, Jarot Sembodo; Barisan (Indonesian Scientific Publication, 2025)
This study evaluates the impact of integrated digital personnel systems namely SIASN, MyASN, and MOLA on administrative efficiency within Indonesia’s civil service. These platforms were introduced as part of a broader e government reform initiative designed to simplify civil servant workflows, reduce delays, and improve transparency. This study specifically evaluates whether the systems shorten turnaround time (TAT) for services including promotions, retirements, and inter-agency transfers. Employing a Difference in Differences (DiD) approach, this research analyzes panel data from regional civil service offices, comparing outcomes in treated and control regions before and after the implementation of digital systems in late 2022. Data sources include timestamped service records from MOLA, performance reports (LKjIP and LAKIP), and SPBE index scores as a proxy for digital readiness. Key outcomes assessed include average TAT and the percentage of services completed within national performance benchmarks. The findings reveal a statistically significant reduction in TAT across all service categories in treated regions. Retirement processing times dropped by an average of 3.4 days, while promotion and transfer services saw reductions of 1.7 and 2.0 days respectively. The percentage of on time promotions increased by 26.4%. Results were more pronounced in regions with higher SPBE scores, underscoring the importance of institutional digital capacity. Robustness checks affirmed the reliability of the findings across various model specifications. The study concludes that digital personnel systems substantially enhance administrative performance when supported by institutional capacity and strategic implementation frameworks. These findings provide actionable insights for policymakers seeking to scale digital reforms across the public sector. By reinforcing efficiency, accountability, and responsiveness, integrated systems represent a critical step toward modernizing governance in Indonesia.